Relationship of serum fasting insulin with gonadotropins in infertile women (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Infertility has become a global health problem in the world wide affecting 8-10% of couple. It is also a matter of social injustice and inequality. Increase level of insulin has been implicated as a cause of infertility. Objective: To find out the association of fasting serum insulin level with gonadotropins in infertile women. Methods: This cross sectional study was conducted in the department of Physiology, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total number of 150 female age ranged from 20 40 years were included in this study. Out of them100 infertile women were selected as study group (group B). Group B was subdivided into group B1 and B2. Group B1 consisted of 50 primary infertile women and group B2 consisted of 50 secondary infertile women. Rest 50 age matched apparently healthy parous women were considered as base line control group A. All the study subjects were selected from out patient department of infertility unit, BSMMU, Dhaka. The control subjects were selected by personal contact. Serum fasting insulin was measured by enzyme-link-immunosorbend assay. Fasting blood glucose and blood glucose two hours after breakfast were measured by glucose oxidase method. The Data were collected in a prescribed data sheet after taking written consent. Statistical analyses were done by unpaired students t tests by SPSS program version 12. The level of significance was calculated and p value